A new method for the capture of surface proteins in Plasmodium falciparum parasitized erythrocyte - Emanuela Ferru; Anntonella Pantaleo; Francesco Turrini (Journal of Infection in Developing Countries)
Introduction: We propose a new method for the selective labeling, isolation and electrophoretic analysis of the Plasmodium falciparum protein exposed on the erythrocyte cell surface. Historically, membrane surface proteins have been isolated using a surface biotinylation followed by capture of biotin-conjugated protein via an avidin/streptavidin-coated solid support. The major drawback of the standard methods has been the labeling of internal proteins due to fast internalization of biotin.